An innovative eccentric ring rolling method for fabricating eccentric rings. (January 2017) - Han, Xinghui; Hua, Lin; Zhou, Guanghua; Wang, Xiaokai; Lu, Bohan
Abstract: Restricted by the working principles, the traditional ring rolling technologies are only fit for fabricating concentric rings while it is difficult for them to fabricate eccentric rings. So this study is devoted to put forward an innovative eccentric ring rolling (ERR) method for fabricating eccentric rings. Firstly, to guarantee ERR successfully, the technological design principles and methods for the rolls, ring workpiece and objective eccentric ring are presented and the rolling conditions in ERR are correspondingly determined. Then, the deforming mechanisms and rolling defects in ERR are analyzed through FE simulations. Finally, to eliminate the rolling defects of uneven axial height distribution of the rolled eccentric ring, the optimization design methods for the ring workpiece and the corresponding rolling conditions are presented. Through simulations and experiments, it is illustrated that qualified eccentric rings with even axial height distribution and highly accurate thickness distribution along the tangential direction can be rolled by ERR and thus the presented ERR method is promising in fabricating eccentric rings. Highlights: An innovative eccentric ring rolling (ERR) method is proposed. Technological design principles and methods and rolling conditions are presented. Deforming mechanisms and rolling defects in ERR are analyzed. Optimization design methods for ring workpiece and rolling conditions are presented. ERR method is promising in fabricating eccentric rings.